53.3 W Visible-Waveband Extra High Power Supercontinuum All-Fiber Laser - Chang Sun; Tingwu Ge; Siyuan Li; Na An; Kang Cao; Zhiyong Wang (IEEE Photonics Journal, 2016)
A visible-waveband extra high power supercontinuum (SC) all-fiber laser is demonstrated. The laser structure includes a seed laser, master power amplifier, and the SC generation system, which usually adopts photonic crystal fiber (PCF) with small mode area as the nonlinear (NL) medium. A repetition frequency multiplier is utilized in the seed laser to adjust the pulse peak power and suppress the NL effects in the amplification process. Additionally, a homemade all-fiber high power mode field adaptor, which is used to couple the pump pulses into the small mode area PCF, works successfully at the incident pulse power of 120 W with high coupling efficiency of 83%. Eventually, 53.3 W visible-waveband extra high power SC fiber laser is obtained with spectrum ranging from 430 to 2400 nm and spectral width below 10 dB flatness exceeding 1700 nm (except pump wavelength). In addition, the visible-waveband power (below 850 nm) takes up about 22% of the total SC power. To the best of our knowledge, this is the highest average power of visible-waveband extra SC source ever reported in such broad spectrum range and high spectrum flatness.